2003
DOI: 10.1046/j.1460-9568.2003.02406.x
|View full text |Cite
|
Sign up to set email alerts
|

The expression of vesicular glutamate transporters VGLUT1 and VGLUT2 in neurochemically defined axonal populations in the rat spinal cord with emphasis on the dorsal horn

Abstract: Two vesicular glutamate transporters, VGLUT1 and VGLUT2, have recently been identified, and it has been reported that they are expressed by largely nonoverlapping populations of glutamatergic neurons in the brain. We have used immunocytochemistry with antibodies against both transporters, together with markers for various populations of spinal neurons, in an attempt to identify glutamatergic interneurons in the dorsal horn of the mid-lumbar spinal cord of the rat. The great majority (94-100%) of nonprimary axo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

93
480
6
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 404 publications
(580 citation statements)
references
References 60 publications
93
480
6
1
Order By: Relevance
“…This antibody labels a single band of appropriate molecular weight (≈62 kDa) in Western blots of synaptic vesicle fractions of rat brains (Synaptic Systems, Goettingen, Germany). In our spinal cord sections the laminar distribution of immunolabeled puncta (high densities in LIII-LV, LVII, and LIX; weaker densities in LI and LII and LVIII) is identical to that previously published by us Mentis et al, 2006) and other authors using this or similar antibodies raised in different species (Todd et al, 2003;Oliveira et al, 2003).…”
Section: Marker Antibodiessupporting
confidence: 88%
See 2 more Smart Citations
“…This antibody labels a single band of appropriate molecular weight (≈62 kDa) in Western blots of synaptic vesicle fractions of rat brains (Synaptic Systems, Goettingen, Germany). In our spinal cord sections the laminar distribution of immunolabeled puncta (high densities in LIII-LV, LVII, and LIX; weaker densities in LI and LII and LVIII) is identical to that previously published by us Mentis et al, 2006) and other authors using this or similar antibodies raised in different species (Todd et al, 2003;Oliveira et al, 2003).…”
Section: Marker Antibodiessupporting
confidence: 88%
“…This antibody labels a single band of appropriate molecular weight (≈62 kDa) in Western blots of synaptic vesicle fractions of rat brains (Synaptic Systems, Goettingen, Germany). In our spinal cord sections the laminar distribution of immunolabeled puncta (high densities in LIII-LV, LVII, and LIX; weaker densities in LI and LII and LVIII) is identical to that previously published by us Mentis et al, 2006) and other authors using this or similar antibodies raised in different species (Todd et al, 2003;Oliveira et al, 2003).Vesicular acetylcholine transporter (VAChT) antibodies: We used two polyclonal antibodies raised in guinea pig and goat, respectively, each against a similar, but not identical, sequence in the C-terminus (see Table 1). By Western blot the guinea pig antibody reacted with a single band in rat brain homogenates that corresponded to the size predicted for VAChT (Chemicon, Temecula, CA).…”
supporting
confidence: 88%
See 1 more Smart Citation
“…The present study examined the relationship of VGlut2, VGlut3 transporters and NKI receptors with fos-I nuclei as both glutamate and NKI receptors have been shown to regulate pelvic reflexes [64,69]. Glutamate is the major excitatory neurotransmitter and recent studies have documented the distribution of glutamate transporters in the lumbosacral cord [2,34,38,51,57,63]. Studies have suggested that VGlut1 and VGlut2 expression is restricted to glutaminergic neurons; however, VGlut3 expression is found not only in glutaminergic neurons but also neurons that contain acetylcholine and serotonin [28].…”
Section: Discussionmentioning
confidence: 96%
“…VGlut2 and VGlut1 immunoreactivity are widely distributed in the central nervous system and are found in some overlapping regions [34,53,63]. Neurons synthesizing VGlut2 have been identified in the ventral medulla, a region that projects to the lumbosacral spinal cord and is involved in regulating pelvic function [42,60].…”
Section: Introductionmentioning
confidence: 99%